Endophytic fungi isolated from Thymus algeriensis with good antimicrobial activities - Amina Zerroug; Nouari Sadrati (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to identify the endophytic fungi associated with medicinal plant Thymus algeriensis and to evaluate their potential for antimicrobial activities. A total of 16 fungi belonging to 6 genera were successfully isolated and identified. The colonization rates ranged from 14.29% to 42.86% and were significantly higher in the roots followed by stems and leaves. Regarding the isolation rates, they were 0.23, 0.14, and 0.1 for the roots, stems, and leaves respectively. Based on the comparison of the morphological characteristics, six genera were identified: Rhizopus, Fusarium, Aspergillus, Alternaria, Phoma, and Penicillium. Fusarium, Phoma, and Alternaria were the most dominant with relative frequencies of 35.5, 28.6, and 14.3% respectively. The fungal endophytes were assessed for their antimicrobial activities using agar plug diffusion method, the best zones of inhibition obtained with the most active endophytic isolates were 20.33 and 20 mm for Fusarium sp. 3, 22.33 and 18.67 mm for Fusarium sp. 5, 23.33 and 25.33 mm for Fusarium sp. 2, and 29.33 and 23 mm for Phoma sp. 4 obtained against Bacillus cereus ATCC 10876 and Staphylococcus aureus ATCC 25923 respectively. The comparison of the averages of inhibition zones obtained against all the pathogenic bacteria showed that the isolates Fusarium sp.3 and Fusarium sp.5 were the most active with mean zones of inhibition of 19.61 and 19.56 mm respectively, followed by Fusarium sp.2 (19 mm) and Phoma sp. 4 (18.61mm). Regarding the antifungal activity, the results showed that the highest inhibition percentages were 60 and 58% obtained by Rhizopus sp. and 51 and 53% obtained by Aspergillus sp. against Fusarium oxysporum f.p. ciccri and Phytophthora infestans respectively. The study concludes the presence of endophytic fungi such as Fusarium, Phoma, Penicillium and Aspergillus associated with Thymus algeriensis that exhibited antibacterial activity. These isolates could serve as potential sources for the isolation of novel antimicrobial agents that may contribute to antibiotic control of antibiotic-resistant bacteria.